Video-Based Motion Analysis Use: A National Survey of Orthopedic Physical Therapists. Issue 10 (31st July 2020) - Hensley, Craig P; Millican, Devyn; Hamilton, Nida; Yang, Amy; Lee, Jungwha; Chang, Alison H
Abstract: Objectives: Motion analysis is performed by physical therapists to assess and improve movement. Two-dimensional video-based motion analysis (VBMA) is available for smartphones/tablets and requires little to no equipment or cost. Research on VBMA use in clinical practice is limited. The purpose of this study was to examine the current use of VBMA in orthopedic physical therapist practice. Methods: Members of the Academy of Orthopaedic Physical Therapy completed an online survey. Questions examined frequency of VBMA use, reasons for use, facilitators/barriers, device/apps used, practice patterns, other certificates/degrees, and demographic information. Results: Among the final analysis sample of 477 respondents, 228 (47.8%) use VBMA. Of 228 VBMA users, 91.2% reported using it for ≤25% of their caseload, and 57.9% reported using their personal device to capture movement. Reasons for using VBMA included visual feedback for patient education (91.7%), analysis of movement (91.2%), and assessment of progress (51.8%). Barriers to use included lack of device/equipment (48.8%), lack of space (48.6%), and time restraint (32.1%). Those with ≤20 years of clinical experience (odds ratio [OR] = 1.83, 95% CI = 1.21–2.76), residency training (OR = 2.49, 95% CI = 1.14–5.43), and fellowship training (OR = 2.97, 95% CI = 1.32–6.66), and those from the West region of the United States (OR = 1.66, 95% CI = 1.07–2.56) were more likely to use VBMA. Conclusions: More than 50% of surveyed orthopedic physical therapists do not use VBMA in clinical practice. Future research should be directed toward assessing reliability and validity of VBMA use by smartphones, tablets, and apps and examining whether VBMA use enhances treatment outcomes. Data security, patient confidentiality, and integration into the electronic medical record should be addressed. Impact: This study is the first to our knowledge to describe the use of VBMA in orthopedic physical therapist practice in the United States. It is the first step in understanding how VBMA is used and might be used to enhance clinical assessment and treatment outcomes.